The Monitoring and Analysis of Threats to Food Safety and Quality Events as Per Various Information Sources Using the Example of a Selected Group of Food Ingredients – Oils and Fats - Magdalena PAZDZIOR; Paulina MITROSZ; Małgorzata KOWALSKA (Communications of International Proceedings, 2021)
The aim of the article was to synthesize and present to consumers the sources of obtaining information about health safety hazards and to raise consumer awareness of making responsible dietary choices. Assuring the safety and quality of food is binding on each and every participant in the chain of food supply as part of the ‘farm to fork’ concept. The analysis of notifications on potentially hazardous food products with regard to a selected group of food products, i.e., fats and oils is based on the data and information from the portals of the State Inspectorate of Agricultural and Food Quality Inspection, Main Sanitary Inspector, RASFF, and Probase360 service. Besides, additional information and opinions regarding the questions discussed are based on a review of literature by other authors. The chosen instance of major components of everyday diet, i.e., fats and oils, serves was to present the types and extent of information about the institutional supervision, which is made available to Polish consumers, inter alia. The diversity of published data is covered on notifications of and warnings against products harmful to health and life depending on the sources of information. Attention is drawn to the real risk to consumer health arising from the diversification of sources and the scope of data. The analysis contained in our study showed that work should continue to standardise the food products inspection system with regard to the health and safety of consumers. Such actions will help to disseminate risk notifications published on the portals of competent institutions.
Keywords: Food Safety; Food Adulteration; Consumer; Oils And Fats; RASFF.